2002
DOI: 10.1021/ja028371y
|View full text |Cite
|
Sign up to set email alerts
|

Polyaniline Nanofibers:  Facile Synthesis and Chemical Sensors

Abstract: Polyaniline nanofibers with uniform diameters between 30 and 50 nm can be made in bulk quantities through a facile aqueous/organic interfacial polymerization method at ambient conditions. The nanofibers have lengths varying from 500 nm to several micrometers and form interconnected networks. Thin films made of the nanofibers have superior performance in both sensitivity and time response to vapors of acid (HCl) and base (NH3).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

31
1,132
4
13

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,635 publications
(1,180 citation statements)
references
References 23 publications
31
1,132
4
13
Order By: Relevance
“…It is reported that the organic precursor of aniline can be converted into electronically conductive carbon through pyrolysis processes at high temperatures 37 . In this process of synthesis of polyaniline, probably carbons are produced from the oxidation process of aniline, which may increase the conductivity of polyaniline.…”
Section: Tem Analysismentioning
confidence: 99%
“…It is reported that the organic precursor of aniline can be converted into electronically conductive carbon through pyrolysis processes at high temperatures 37 . In this process of synthesis of polyaniline, probably carbons are produced from the oxidation process of aniline, which may increase the conductivity of polyaniline.…”
Section: Tem Analysismentioning
confidence: 99%
“…For each experiment, the multi-pen tips 5 were dipped into inkwells and then initial contact made with the surface prior to patterning to remove excess ink from the tip. After this initial "bleeding" step, it was possible to stably pattern dots across all 12 pens for well in excess of over an hour, which amounted to 40 µm dot arrays (comprising 9x9 dots) being able 10 to cover an approximate surface area of 2 x 2 mm (each pen is separated by ~60 µm).…”
Section: Dpn Pattering Of Pedot:pss Inksmentioning
confidence: 99%
“…In particular, 35 nanoscale CP sensors for detection of gases and biomolecules can provide relatively higher sensitivity and faster response times than conventional macro-and microsized sensors. [2][3][4][5] Thus miniaturization of chemical and biological sensors is desirable and provides further opportunities for lowering detection limits, 40 reducing volumes needed for sensing, enhancing selectivity, increasing portability and in vivo applicability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, they can be used in a variety of possible sensing applications. By exploiting their chemical selectivity, polymer nanowires can be used to detect a wide range of chemical compounds including toxics gases, metal ions, and DNA (Huang et al 2003;Wang et al 2002;Ramanathan et al 2005). Polymer nanowires have been studied for use as chemical sensors, biosensors, organic light emitting diodes, and organic solar cells (Huang et al 2003;Liu et al 2004;Ramanathan et al 2005).…”
Section: Introductionmentioning
confidence: 99%